Analyzing the Impact of ERP System Integration on Customer Satisfaction in Puregold Monumento - Villaruz, Ramcy; Aguas, Carlo Bryle; Besonia, Rizalyn; Cinco, Kyla; Cloma, Nicole; Palmeras, Cristan; Magat, Niño; Pasagui, Ryan Rey; Meñez, Maria Christina; Tillo, Jeffrey (International Journal of Education, Research, and Innovation Perspectives, 2026)
Enterprise Resource Planning (ERP) systems are increasingly used in retail to improve service efficiency, accuracy, and responsiveness through integrated and automated processes. In large supermarkets, ERP integration can influence the customer experience at critical touchpoints such as inventory visibility, cashiering reliability, transaction speed, and issue resolution. This study examined how ERP system integration shapes customer satisfaction in Puregold Monumento. A quantitative descriptive–correlational design was utilized. Data were collected through a structured survey questionnaire distributed via Google Forms to Puregold Monumento customers (N = 357). Descriptives summarized perceptions and satisfaction, while regression analyses tested the predictive influence of ERP integration and its dimensions on customer satisfaction. Customers generally agreed that ERP integration is evident across dimensions—data accuracy (M = 3.94), system reliability (M = 3.72), user training (M = 3.88), and process automation (M = 3.83). Overall satisfaction was also high (M = 3.95), though respondents strongly noted that the system could still be improved (M = 4.08), particularly regarding service speed consistency. ERP integration significantly predicted customer satisfaction (R = .874, R² = .763, p < .001). In the dimension-level model, process automation was the strongest predictor (β = .355), followed by data accuracy (β = .229), user training (β = .204), and system reliability (β = .172). ERP integration is a central driver of customer satisfaction in Puregold Monumento, with automation-related convenience contributing most strongly. However, gaps in stock visibility, occasional system freezes, and complex transaction handling suggest that integration benefits are not uniformly experienced. The supermarket should improve real-time inventory synchronization, strengthen POS stability, enhance scenario-based staff training, and align automation with queue management to ensure consistent speed. Future research may extend the model across branches and use mixed methods to explain variation across customer segments.